2003
DOI: 10.1128/jvi.77.22.11992-12001.2003
|View full text |Cite
|
Sign up to set email alerts
|

Telomere Repeat Binding Factors TRF1, TRF2, and hRAP1 Modulate Replication of Epstein-Barr Virus OriP

Abstract: Epstein-Barr virus OriP confers cell cycle-dependent DNA replication and stable maintenance on plasmids in EBNA1-positive cells. The dyad symmetry region of OriP contains four EBNA1 binding sites that are punctuated by 9-bp repeats referred to as nonamers. Previous work has shown that the nonamers bind to cellular factors associated with human telomeres and contribute to episomal maintenance of OriP. In this work, we show that substitution mutation of all three nonamer sites reduces both DNA replication and pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
82
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(86 citation statements)
references
References 76 publications
(88 reference statements)
3
82
1
Order By: Relevance
“…The inspection of the EBV origin of replication reveals a TRF1 or TRF2 binding site (TTA GGG TTA) repeated three times, and TRF1, TRF2 and RAP1 were found to bind there, in a search for binding factors by affinity chromatography. 106,107 In this system, TRF2 was shown to be important for the recruitment of specific replication factors, in particular the viral origin binding protein EBNA1, themselves essential for the effective replication of the virus. Further work revealed that interactions between TRF2 and the ORC complex, essential for the initial recognition of DNA replication origins, were important in this context, 108 and were also at play at telomeres.…”
Section: As Trf2mentioning
confidence: 99%
“…The inspection of the EBV origin of replication reveals a TRF1 or TRF2 binding site (TTA GGG TTA) repeated three times, and TRF1, TRF2 and RAP1 were found to bind there, in a search for binding factors by affinity chromatography. 106,107 In this system, TRF2 was shown to be important for the recruitment of specific replication factors, in particular the viral origin binding protein EBNA1, themselves essential for the effective replication of the virus. Further work revealed that interactions between TRF2 and the ORC complex, essential for the initial recognition of DNA replication origins, were important in this context, 108 and were also at play at telomeres.…”
Section: As Trf2mentioning
confidence: 99%
“…The replication of oriP plasmids is significantly inhibited in cells hypomorphic for ORC2 or overexpressing the cellular protein geminin that inhibits full assembly of the pre-RC, confirming EBV's reliance on these cellular pathways for the replication of its own genome (Dhar, Yoshida et al 2001). While a pair of EBNA1-binding sites is sufficient for DNA synthetic function, the presence of the nonamer elements flanking the origin and the binding of TRF2 to them stimulates the initiation of DNA synthesis from that origin (Deng, Lezina et al 2002;Deng, Atanasiu et al 2003;Atanasiu, Deng et al 2006). Some of this stimulation likely results from TRF2's increasing EBNA1's apparent affinity for DS; in addition, some may also result from the direct interaction of TRF2 with the BAH domain of ORC1, allowing increased recruitment of ORC1 to DS at the G1/S border of the cell cycle (Ritzi, Tillack et al 2003;Atanasiu, Deng et al 2006).…”
Section: Ebv Usurps Cellular Factors For Its Own Endsmentioning
confidence: 90%
“…Flanking the pairs of EBNA1-binding sites of DS are three 9bp elements that resemble telomeric repeats, and have been termed nonamers (Niller, Glaser et al 1995), (Yates, Camiolo et al 2000). Lieberman and colleagues have shown in several studies that these elements are bound by cellular proteins associated with the telomeres, including TTAGGG-Repeat binding Factors (TRF1, TRF2), the human repressor activator protein 1 (hRap1), and tankyrase (Deng, Lezina et al 2002), (Deng, Atanasiu et al 2003), (Deng, Atanasiu et al 2005). Deletion or mutation of the nonamer elements decreases by twofold the average number of plasmids maintained per cell (Deng, Lezina et al 2002), (Deng, Atanasiu et al 2003).…”
Section: Cis Elements Of Ebv That Contribute To Dna Replicationmentioning
confidence: 99%
See 2 more Smart Citations